2007
DOI: 10.1007/s10532-007-9164-0
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of degradation of phenol in a fluidized bed bioreactor with a cyclodextrin polymer as biofilm carrier

Abstract: This work is focused on the evaluation of a beta-cyclodextrin polymer as a carrier medium in a fluidized bed bioreactor treating aqueous phenol as a model pollutant. The insoluble polymer support was obtained in the shape of spherical beads by crosslinking beta-cyclodextrin with epichlorohydrin. A batch of swollen polymer particles was loaded into the reactor and inoculated with a mixed bacterial culture. Bacterial growth on the polymer beads was initially stimulated by glucose addition to the medium, and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 24 publications
1
24
0
1
Order By: Relevance
“…Since the stagnant bed height scarcely increased after the whole colonization of the support media, the thickness of the growing biofilm remained quite stable throughout the study. This is a significant difference with fluidized bed bioreactors in which biofilm thickness can increase appreciably (Sevillano et al [8]). Phenol loading rates in the DT-SBB operation with CDP bioparticles.…”
Section: Biofilm Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the stagnant bed height scarcely increased after the whole colonization of the support media, the thickness of the growing biofilm remained quite stable throughout the study. This is a significant difference with fluidized bed bioreactors in which biofilm thickness can increase appreciably (Sevillano et al [8]). Phenol loading rates in the DT-SBB operation with CDP bioparticles.…”
Section: Biofilm Growthmentioning
confidence: 99%
“…First, the DT-SBB is a fixed biofilm reactor and the other was a suspended biomass system, and it is wellknown the larger resistance of the former compared to the latter (Sá and Boaventura [14]). Furthermore, the use of a hydrogel support with proven sorption ability towards phenol (Romo et al [15]) would enhance the protection of the biofilm from shock-loading (Sevillano et al [8]). After the saturation point was reached, as the phenol removal capacity dropped abruptly, the inlet load was reduced to 0.93 kg/m 3 d in order to recover the process efficiency.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Two-phase fluidised-bed bioreactors are also applied in experimental studies on the determination of effective diffusion coefficients in biofilms and the application of polymers as biofilm carrier (Sevillano et al, 2008). In 2000, in Europe and the USA, there were more than 80 two-phase fluidised-bed bioreactors in industrial use (Rodgers and Zhan, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, biodegradation of phenol in wastewater is generally more cost-effective than the physic-chemical treatment processes (Loh et al 2000). Conventionally, aerobic biological methods have been used for the treatment of phenolic wastewater (González et al 2001;Bajaj et al 2008;Sevillano et al 2008). However, due to their lowenergy requirement and sludge yield, anaerobic biological methods are now being preferred (Veeresh et al 2005) despite they have been reported since late 80's (Table 1).…”
Section: Introductionmentioning
confidence: 99%